DEVELOPMENT FACTORS OF COMPETENCE LEVEL OF TEACHER OF TECHNOLOGY - M. M. Ahmedov (Zeta Repository, 2023)
In this article, as factors for the development of the level of competence of the technology teacher, the increase in the level of knowledge of schoolchildren and the effectiveness of education and training processes, the effectiveness of pedagogical research in the direction of a systematic approach, ensuring the activity of students in the organization and management of pedagogical processes, and the performance of tasks set according to specific goals, the individual in the process of motivating them -activity approach was studied as important factors.